The impact of EC+ as a multimodal support in intervention for children with autism spectrum disorder: a technological alternative. - Zurita Díaz, Antonio Javier; Calleja Reina, Marina (Disability & Rehabilitation: Assistive Technology, 2025)
Purpose: This study aims to evaluate the effectiveness of Enhancing Communication Plus (EC+), an augmentative and alternative communication (AAC) technological support system, in improving communication, social interaction, and behavior in children with Level 3 autism spectrum disorder (ASD) and complex communication needs. The intervention combines EC+ with aided augmented input to enhance expressive and receptive communication. Methods: A quasi-experimental design was conducted over 16 weeks with 18 children aged 6 to 12 diagnosed with Level 3 ASD. Participants engaged in therapy sessions using EC+ within a structured intervention framework. Communication, social skills, and behavioral outcomes were assessed at three evaluation moments using the Vineland-3 scale. Data analysis was performed using SPSS, with statistical tests including repeated-measures ANOVA. Results: Significant improvements were observed across all measured domains. Participants demonstrated enhanced communicative abilities, increased social interaction, and a reduction in disruptive behaviors. The multimodal features of EC+ contributed to engagement and learning, making communication more accessible and intuitive. Conclusion: The findings highlight the potential of EC+ as an effective AAC tool for children with Level 3 ASD. Its multimodal features offer a structured and engaging approach that enhances communication, socialization, and behavior. Future research should explore its comparative effectiveness with other AAC supports and ICT-based tools. IMPLICATIONS FOR REHABILITATION: EC+ is an innovative AAC technological support developed at the University of Málaga, offering multimodal functions for the entire vocabulary, making it highly beneficial for intervention. The integration of EC+ with aided augmented input provides an effective strategy for improving expressive and receptive communication in children with Level 3 ASD and complex communication needs. The multimodal features of EC+ facilitate greater engagement and interaction, supporting the development of social skills in therapeutic settings. By offering structured and intuitive communication support, EC+ helps decrease disruptive behaviors-related behaviors, promoting more adaptive responses.